Les zones de production du fer en Bourgogne-Franche-Comté : une approche sur la longue durée par le radiocarbone - Marion Berranger; Marc Leroy; Hervé Laurent (Gallia)
As early as the 1980s, archaeological surveys have been carried out in the north-east and centre-east of France in order to inventory ancient smelting sites, whose installations are marked by accumulations of production waste. More than a thousand sites, very unevenly distributed over this territory, were inventoried. A few radiocarbon dates and the collection of ceramic material made it possible to propose an initial chronology. Roman period productions appeared to be the best known and most widespread. In the early 2000s, new radiocarbon dates made it possible to re-evaluate the importance of medieval siderurgical production, particularly in the Pays d’Othe and in the area known as Berthelange, south-west of Besançon. The chronological data, however, remained too limited to attempt to outline the evolution of iron ore smelting activities in this geographical area.The spatial framework of this article is the present-day Burgundy-Franche-Comté region, within which more than 5,000 unevenly distributed smelting sites are currently known. The largest concentrations are to be found in the western part of Burgundy, in the natural regions of Puisaye, Pays d’Othe and Sénonais, in Morvan-Auxois, and in Franche-Comté in the so-called Berthelange area. Smaller groups are also known in the Nivernais and Mâconnais. On the basis of these inventories, a collective research programme began in the 2010s, in order to specify the chronology of the smelting areas in Burgundy-Franche-Comté. Its objective is to define the technical characteristics of the metallurgical operations and to date a large number of these workshops by using radiocarbon dating, as systematically as possible, on charcoal taken from stratigraphy or within metallurgical slag.One hundred and eighty sites were studied and sampled. Thus, and taking into account previously acquired samples, more than 159 new radiocarbon dates were obtained, making it possible to identify 210 exploitable dates from 159 sites. The purpose of this article is to present the results of this new work which, by correlating dates from the workshops with the typology of the sites and the waste. This new approach has substantially modified our perception of the chronology of iron production in this region.The first part of this article presents the results of the research carried out in the different production areas, while recalling the achievements of previous work. The second portion is devoted to the studies carried out on smelting slag. The last part proposes an attempt at interpreting the evolution of smelting activities. Four main chronological phases between the 8th century BC and the 15th century AD have been distinguished. The processing of ore into iron is now clearly documented from the Early Iron Age onwards in the western and eastern regions of this area. During the middle and final phases of the Second Iron Age and throughout the Roman Period, this production continuously developed in the western part of the area studied (Puisaye, Sénonais - Pays d’Othe, Nivernais). Grouping of production for the Roman period is revealed to have been vastly different from the long-envisaged hypothesis of an activity dispersed over a large north-eastern quarter of France. A break in the activity of these “western” production areas appears to have occurred in the 4th and 5th centuries AD. They were, however, active again during the early Middle Ages and other areas that had not previously existed appeared in the data (Morvan-Auxois, Mâconnais, the Berthelange area). With the exception of the Berthelange area, whose production is concentrated during the Merovingian period, the activity is continuous throughout the medieval period in all the other areas of production. Thus, smelting activity is more widely represented throughout the territory during this period than for the previous Roman one. Thus, the large production areas known historically in this geographical area from the 13th-14th centuries onwards possess clear predecessors.